Predicting and Preventing Sudden Cardiac Death in the Young - Erika Maharani (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Sudden cardiac death (SCD) is an unexpected death condition and occurs with unknown causes or cardiac condition. The SCD incidence at young age is a rare condition but when this condition happens it become traumatic event for both family and community. Incidence rate of death on 1-35 years old is around 0.8-2.8/100.000 each year. This number also varies according to age and sex. Death incidence on 1-4 years old is more common than on 5-10 years old group. This number is increasing after 15 years old, where age of 31-35 years has 10 fold risk of SCD compared to 1-10 years old group. Ratio of SCD in men and woman are 2: 1. Early detection of underlying heart disease is the most important action of preventio. If young people are known to have a risk of SCD, the lifestyle changing and appropriate medical therapy, including implantation of implantable cardioverter defibrillator, according to risk stratification must be done.